Transport and storage dynamics of 30% In-rich InGaN/GaN MQW LED p-i-n structure - Ozdemir, Orhan; Bozkurt, Kutsal; Kuruoglu, Neslihan Ayarci; Bas, Hanife; Alshehri, Bandar; Dogheche, Karim; Gaimard, Quentin; Ramdane, Abderrahim; Dogheche, Elhadj (IOP Publishing Ltd, 2019)
DC and AC electrical characteristics of an InGaN/GaN multi-quantum well light emitting diode based on PIN structures were investigated through temperature-dependent current-voltage (I-V-T) and admittance-temperature-frequency (Y-T-omega) measurements within 80-375 K temperature interval. Multi-step tunneling was discerned as a carrier conduction mechanism for whole reverse and small forward biases at the high-temperature side in the studied temperature interval while hopping conduction at the low side. Electron and hole as the tunneling carriers were identified through activation energy, 110 meV and 60 meV respectively. The values were determined from I-V-T/C-T-omega measurements in conjunction with conductance of quantum well itself and consisted with the reported activation energy; 120-220 meV for electrons, 50-80 meV for holes.
Keywords: gallium nitrate; LED; multiple quantum well; tunneling; quantum well conductance; SPECTROSCOPY; TEMPERATURE; VOLTAGE; TRAPS; POWER; GAN; Physics